(3WQb EOGQI GdeQGab GdYGeI, GdeDSSI GdYGeI h GdNUNUIs - (3hdjO MjOQ(B, (3LGHQs ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2009)
(3GdGSdhH GdJYGbOj , ?CSdhH GdTQcGJ , GdeDSSSI GdYGeI Hjf GdbOje h GdMGVQ , GdfXGe GdbGfhfj ddeDSSGJ GdYGeI , GdeDSSI GdYGeI JLQHI eThgI , XGgQI GdNUNUI (B: (3GdNUNUI JMOj bGfhfj , GSJQGJjLj h eDSSGJj , GdNUNUI Hjf GdfXQjI h GdhGbY (B.s
(3eQGLY U(B.157s
Keywords: (3GdbWGY GdNGUs; (3GdeDSSGJ GdYGeIs; (3GdeQGab GdYGeI `` GOGQIs